2012
DOI: 10.1016/s1734-1140(12)70884-8
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol and nitric oxide modulate expression of glucocorticoid receptor in the rat adrenal cortex

Abstract: Obtained findings are the first to demonstrate localization and distribution of the GR throughout the rat adrenal cortex and to suggest that ethanol as well as endogenous NO may modulate adrenocortical expression of this steroid receptor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Specifically, reduced GR nuclear translocation and increased cytoplasmic retention of GR under melatonin treatment causes the up-regulation of NRF2 (Kratschmar et al 2012;Singh and Haldar 2016). Moreover, decreased liver antioxidant enzyme activity (SOD, CAT and GPx) generally contributes towards reducing total GR levels and GR activation (GR nuclear translocation) (Liu et al 2008;Skuza et al 2011;Djikic et al 2012;Wei et al 2013). In this study, the expression levels of hepatic nuclear GR proteins were negatively correlated with hepatic CAT and GPx activity.…”
Section: Discussionmentioning
confidence: 56%
“…Specifically, reduced GR nuclear translocation and increased cytoplasmic retention of GR under melatonin treatment causes the up-regulation of NRF2 (Kratschmar et al 2012;Singh and Haldar 2016). Moreover, decreased liver antioxidant enzyme activity (SOD, CAT and GPx) generally contributes towards reducing total GR levels and GR activation (GR nuclear translocation) (Liu et al 2008;Skuza et al 2011;Djikic et al 2012;Wei et al 2013). In this study, the expression levels of hepatic nuclear GR proteins were negatively correlated with hepatic CAT and GPx activity.…”
Section: Discussionmentioning
confidence: 56%
“…Moreover, 11βHSD can effectively control the active GC concentration in local tissue (represented by cortisol in humans and corticosterone in rodents) by catalyzing reciprocal transformation between inactive and active GCs 18 . Corticoid receptors (CRs), including the mineralocorticoid receptor (MR) and glucocorticoid receptor (GR), are ligand-dependent nuclear transcription factors 19 . The insulin-like growth factor 1 (IGF1) signaling pathway is the core of the endocrine regulatory system, modulates adrenal cell proliferation, differentiation and metabolism, which play important roles in morphology and functional development 20 , 21 .…”
Section: Introductionmentioning
confidence: 99%
“…StAR is present within mitochondria in all tissues that produce steroids [27][28][29]. StAR plays an essential role in steroid synthesis by regulating cholesterol transport from the outer to the inner mitochondrial membrane, making it available to the enzymes that convert cholesterol to the different adrenal steroids.…”
Section: Resultsmentioning
confidence: 99%
“…To our knowledge very little information exists relevant to potential paracrine or autocrine feedback of glucocorticoids within the ZF. Entering the terms glucocorticoid receptor and zona fasciculata in PubMed produced only one report [29]. This paper indicated that it was the first report to demonstrate localization and distribution of GR throughout the rat adrenal cortex and reported that endogenous nitric oxide (NO) may modulate adrenocortical expression of this steroid receptor.…”
Section: Discussionmentioning
confidence: 99%